You only live twice - Broccoli, Albert R.; Salzman, Harry; Fleming, Ian 1908-1964; United Artists Corporation ([Burbank, Calif. Warner Home Video, 1967)
James Bond adventure set in Japan, where the SPECTRE organization, headed by Blofeld, plots to incite the world's major powers into war against each other.
VHS.
Released as motion picture in 1967.
Based on the novel by Ian Fleming.
Screenplay by Roald Dahl ; produced by Harry Salzman and Albert R. Broccoli ; directed by Lewis Gilbert.
Sean Connery, Akiko Wakabayashi, Tetsuro Tamba, Mie Hama, Teru Shimoda, Karin Dor.
Keywords: Bond, James (Fictitious characters) -- Drama; Spy stories, English -- Film and video adaptations; Feature films; Spy films